Comparative Yield Performance of Rice Production Under Organic and Inorganic Fertilizer Application - Dollison, Mohammad D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The technology demonstration on rice production under organic and inorganic fertilizer application was conducted to determine which of the identified treatments would give better rice growth and yield and showcase the technology to the farmers. The study was composed of three treatments. Treatment A – Inorganic Fertilizer (120-60-60); Treatment B – ½ of 50% Inorganic + 50% Vermicast RR; Treatment C – 25 bags of vermicast as organic fertilizer. An area of 778.18 square meters was divided into three plots with a measurement of 19.30 meters in length and 12.44 meters in width (19.30m x 12.44m). Between plots was provided with a 1-meter distance for the passageway and drainage for excess water. The research made use of frequency and mean to determine the growth and yield performance of NSIC Rc 160 (Tubigan 14) as applied with organic and inorganic fertilizers. Treatment variation was analyzed using one-way ANOVA. The result of the study shows that the application of inorganic and organic fertilizers gave a comparable performance in terms of growth and yield performance. However, in terms of a cost analysis of using inorganic and organic fertilizers, it is more economical to use organic fertilizer than inorganic fertilizer. It further showed that the lower the cost of production, the higher the net income of the rice production under organic fertilizer application. The researcher further concluded that the application of vermicast alone as a fertilizer source or a combination of inorganic and organic fertilizers is more cost-efficient in rice production than purely inorganic fertilizer application.